Antidiabetic assessment of mango and soursop leaves bioactive phytochemical formulation on streptozotocin-induced rat model - Churchill Chisom Ogbonna; Samuel Chidi Iwuji; Taofik Oladimeji Azeez; Raymond Maduabuchi Okoronkwo; Tochukwu Nze Ugorji; Christian O. Asadu (Clinical Phytoscience)
Abstract Background It is no controversy that plant-based herbal formulations are used for their medicinal properties, since time so long to remember but the identification, isolation and characterization of the bioactive constituents for specific health therapy remains an issue of concern in public domain owing to the challenges of low yield, painstaking isolation, and purification process from plant matrix.This work demonstrates the antidiabetic activities of the bioactive derivatives of mango and soursop leaves on streptozotocin-induced albino Wistar rat models. Methods Cold maceration was used for phytochemical extraction, with ethanol as the solvent of extraction, followed by phytochemical screening tests of the ethanolic extracts and quantitative analysis and isolation of phytochemicals that possess strong antidiabetic activities. GCMS of the samples mass spectra was analysed and gravimetric methods used for the extraction of the bioactive constituents for use as the therapeutic formulations in-vivo at 100 mg/kg b.w in three different ratios 75:25, 25:75 and 50:50. In -vivo rat models were acclimatized, induced with STZ and grouped into seven (7). FBS and body weight of models were taken at seven days intervals. OGTT, LD50, Lipid profile, Biochemistry of antioxidants and insulin contents were analysed. Histopathology of the liver, kidney and pancreas as well as FTIR analysis of the combination therapy was conducted. Results Preliminary screening of both leaf samples revealed the presence of alkaloids, flavonoids, tannins, phenols, terpenoids and saponins, and quantitative analysis showed high yield for saponins and flavonoids of both samples of mango and soursop leaves. Further analysis revealed strong antidiabetic activities of the saponin and flavonoid fractions thus a GCMS analysis of the saponin fraction for mango leaves and flavonoid fraction for soursop leaves which showed succinic acid and hexamethyl cyclotrisiloxane as the predominant organic compounds respectively. Succinic acid and hexamethyl cyclotrisiloxane gave high yields 88.55% and 67.38% respectively. FTIR showed the presence of pharmaceutically active functional groups. LD50 of 1264.91 mg/kg b.w was calculated. Weekly FBS and body weight results showed an inverse relationship, OGTT showed the highest percentage glucose reduction capacity and Lipid profile revealed high HDL levels. In-vivo biochemical analysis of serum revealed high SOD, CAT, GPX, GSTs and IC as well as a regenerating histo-architecture of the liver, kidney and pancreas. Conclusion The bioactive phytochemical derivatives of mango and soursop leaves extract proved safe at doses ≤ 1000 mg/kg b.w and the test formulation exhibited remarkably statistically significant (P < 0.05) glycemic control at a dose of 100 mg/kg b.w relative to the standard plant derived drug, metformin, 500 mg/kg b.w) as reference control and Glibenclamide, 5 mg/kg b.w, as positive control. This was corroborated by the extracts high percentage glucose reduction capacity and results of oral glucose tolerance test, particularly with group V and VII. Efficacy of the test formulations exhibited significant in-vivo protective potentials as evidenced by high in-vivo, with statistically conclusive difference activity levels of high-density lipoprotein, superoxide dismutase, catalase, glutathione peroxidase, glutathione -s transferase and insulin concentration. Histopathological configuration of the liver, kidney and pancreatic samples revealed a regenerative tendency in the histo-architecture. This is associated with the predominance of ether and tertiary amine, and ester and primary amines functional groups in the extracts formulations of group V and group VII samples respectively, which gave the treatment regimen the ability to reduce surface tension between two immiscible samples thereby stabilizing the extract mixture, serve as free radicals’ scavenger, modulate solubility and provide interactions that trigger responses thus enhancing synergy of the extract’s combination therapy.